Creative Imagination in Islamic Education Neuroscience Perspective - Nyimas Wulandari; Suyadi Suyadi (IAIN Batusangkar, 2022)
This article aims to develop creative imagination thinking in students with neuroscience-based learning based on Islamic learning. This research is a type of librarian research. In the golden period that occurs for children, all aspects can develop rapidly so that it requires stimulation that can optimize it, one of which is creative imagination. As it is known that this creative imagination has not been developed too much in education, even imagination is a distraction in children's learning. However, many historical scientists put forward creative imagination. This shows that creative imagination is not a learning disorder but a way to optimize thinking patterns and brain function to the fullest. Such as activities in learning that can provide a stimulus to children's imaginations such as playing music, singing prayers, making unique paintings, etc